Chemical Frost Protection of Road Surfaces: A Laboratory Investigation. Issue 1 (January 2020) - Fjærestad, Janne Siren; Klein-Paste, Alex; Wåhlin, Johan
Anti-icing chemicals are commonly used to protect against hoar frost formation on roadways and bridges. Because of their negative impact on both environment and infrastructure, their use should be optimized. During conditions for hoar frost formation, this means that good knowledge is needed about when it is necessary to apply chemicals, and the corresponding protection time. A laboratory setup has been used to study the freezing process for a salted road surface during conditions for hoar frost formation, and a description of the process is given. It has been observed that freezing starts in the top layer of the applied solution, indicating the occurrence of a concentration gradient owing to accumulation of water molecules in the top layer. A British pendulum was used to simulate the mechanical load of traffic. The pendulum successfully destroyed the ice up to a certain ice fraction. This ice fraction was seen to depend on the amount of salt solution applied to the test sample. Finally, it has been illustrated how the maximum ice fraction can be used to calculate the amount of water allowed to be added to the road surface, and estimates of the protection time are given.